The Importance of Autonomy of European Union Member States with regard to the Use of Genetically Modified Organisms on the Right to Healthcare – An Analysis of Judgements of the Court of Justice of the European Union - Meško Kuralt Katja (LeXonomica, 2022)
The European Union Member States (hereinafter: EU MS) have the possibility of restricting or banning the cultivation of GMOs under the Directive 2015/412 but under certain conditions. EU MS must also pay attention to the provisions of the Treaty on the Functioning of the Euro-pean Union or Treaty Establishing the European Community (hereinafter: TFEU), the provi-sions relating to the free movement of goods, which is one of the key objectives of the func-tioning of the European Union. This contribution is based on the data obtained from an analy-sis of Court of Justice of the European Union (hereinafter: CJEU) cases concerning the use of genetically modified organisms (hereinafter: GMO(s)). The analysis highlights the link between environmental risk assessment and the right to healthcare. The purpose of this paper is to make the individual aware of the possibilities they have regarding the use of GMOs. Povzetek. Države članice Evropske unije lahko v skladu z Direktivo 2015/412 omejijo ali prepovejo gojenje GSO, vendar pod določenimi pogoji. Države članice EU morajo upoštevati tudi določbe Pogodbe o delovanju Evropske unije in določbe v zvezi s prostim pretokom blaga, ki je eden od ključnih ciljev delovanja Evropske unije. Prispevek temelji na podatkih, pridobljenih na podlagi analize zadev Sodišča Evropske unije v zvezi z uporabo GSO. Analiza poudarja povezavo med oceno tveganja za okolje in pravico do zdravstvenega varstva. Namen tega prispevka je seznaniti posameznika z možnostmi, ki jih ima v zvezi z uporabo GSO.